1984
DOI: 10.1128/aac.26.5.652
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure liquid chromatographic method for analysis of cephalosporins

Abstract: A high-pressure liquid chromatographic method is described for the analysis of a wide range of cephalosporin congeners, using only three reagents for extraction and drug analysis. Plasma was treated with cold methanol-0.1 M sodium acetate to precipitate protein. Cephalosporins were resolved on a C-18 reverse-phase column, utilizing a mobile phase of various percentages of 0.01 M sodium acetate and acetonitrile-methanol. Compounds analyzed included cephalexin, cefamandole, cephalothin, cefotaxime, cefazolin, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…Two methods introduced for cefaclor were based on protein precipitation. In the first method, the supernatant was directly quantified by RP-HPLC after precipitation with cold methanol-0.1 M sodium acetate (65). Recovery was excellent, and the detection limit was 0.2 Fkg/ml.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two methods introduced for cefaclor were based on protein precipitation. In the first method, the supernatant was directly quantified by RP-HPLC after precipitation with cold methanol-0.1 M sodium acetate (65). Recovery was excellent, and the detection limit was 0.2 Fkg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Two RP-HPLC methods were reported for cephaloridine in plasma or urine during this review period (36,65). One of the methods was applied to rat urine samples contaminated with feces and diet pellets (36).…”
Section: Methodsmentioning
confidence: 99%
“…When the gasket is placed with the Millipore filter in contact with body tissues, the filter allows the free diffusion of interstitial fluid into the chamber but is impermeable to bacteria. The 6.64 x 106 CFU/ml (n = 30) as determined by the plating of serial dilutions in brain heart infusion agar. The concentration of E. coli averaged 1.34 x 107 CFU/ml (n = 12).…”
Section: Methodsmentioning
confidence: 99%
“…Cephalosporin antibacterial used in the treatment of infections due to susceptible Gram-positive and Gram-negative bacteria, including infections of the abdomen, bones and joints, CNS, skin and skin structure, genito-urinary tract (including gonorrhoea) and respiratory tract, in gynaecological infections, and in early Lyme disease [2,3]. Literature survey revealed that several HPLC [4][5][6][7][8][9][10][11], HPTLC [12] and spectrophotometric methods [13][14][15][16][17][18] have been used for determination of Cefotaxime Sodium. Paracetamol is chemically 4-hydroxy acetanilide.…”
Section: Introductionmentioning
confidence: 99%